Improving Students’ Vocabulary Understanding by Using Vocabulary Self-Collection Strategy - Azmi, Ulul (STKIP Harapan Bima, 2021)
This study aimed at finding out the implementation of vocabulary self-collection strategy in improving students’ vocabulary mastery. The research design used Classroom Action Research with qualitative and quantitative approaches. The subjects of this research was students of VIII A class of SMPN 4 Selong in academic year 2021/2022 with total number of the subject 25 students. The research used multiple choice test as the instrument of the research. The data collecting procedure used four steps such; planning, acting, observing, and reflecting. The data analysis used minimum criteria with standard score 75 by taking classical completeness analysis. Based on the data analysis of the research analysis was gotten the score of the students’ improvement from first to the second cycles with the average score 75 to 93,2. Therefore, it took conclusion that there was improvement of students’ vocabulary mastery by using Vocabulary Self-Collection Strategy